Comparing results from long and short form versions of the Parkinson's disease questionnaire in a longitudinal study. Issue 11 (November 2015) - Jenkinson, Crispin; Clarke, Carl; Gray, Richard; Hewitson, Paul; Ives, Natalie; Morley, David; Rick, Caroline; Wheatley, Keith; Williams, Adrian
Abstract: Background: The purpose of this study was to determine the extent to which summary index scores from the short form Parkinson's Disease Questionnaire (PDQ-8) replicate those from the parent form (PDQ-39) in a longitudinal study. Methods: Longitudinal data gained from the PD-MED trial were examined (n = 1867), to determine the extent the PDQ-8 replicates results from the PDQ-39 at baseline and follow up. The sensitivity to change of the PDQ-8 was also compared with that of the PDQ-39. Finally, results on the two measures were compared with those from the Hoehn and Yahr (HY) clinical staging scale. Results: Results of the Single Index summary score gained from the PDQ-8 were found to closely replicate those gained from the PDQ-39 at each of the three time points. Furthermore at each time point the intraclass correlation coefficient between the two measures was very high (ICC range 0.93–0.96). Similarly, the two measures gave very similar accounts of change (e.g. from baseline to follow up at one year effect sizes were 0.18 for the single index calculated using the PDQ-39, and 0.09 when calculated using the PDQ-8). Similar levels of correlation were found between the two indices when correlated with the HY scale. Conclusions: The PDQ-8 closely replicates results gained from the PDQ-39 when calculating single indices. In instances where a single summary score of the impact of PD on self-reported quality of life is needed, it is likely the PDQ-8 will provide reliable and accurate information. Highlights: The PDQ-39 is the most widely used patient reported outcome measure in trials in PD. A short form has been developed (PDQ-8) to provide the Summary Index of the PDQ-39. The PDQ-8 closely replicates results from the PDQ-39 longitudinally. PDQ-8 may be used as a primary or secondary outcome in longitudinal studies.